The effect of normobaric oxygen in patients with acute stroke: a systematic review and meta-analysis. (3rd June 2018) - Ding, Jiayue; Zhou, Da; Sui, Meng; Meng, Ran; Chandra, Ankush; Han, Jie; Ding, Yuchuan; Ji, Xunming
ABSTRACT: Background Normobaric oxygen (NBO) has received considerable attention due to controversial data in brain protection in patients with acute stroke. This study aims to analyze current data of NBO on brain protection as used in the clinic. Methods We searched for and reviewed relevant articles and references from Pubmed, Medline, Embase, Cochrane, and Clincialtrials.gov that were published prior to October 2017. Data from prospective studies were processed using RevMan5.0 software, provided by Cochrane collaboration and transformed using relevant formulas. Results A total of 11 prospective RCT studies including 6366 patients with acute stroke (NBO group, 3207; control group, 3159) were enrolled in this analysis. △NIHSS represented the values of NIHSS at 4, 24 h, or 7 days post-stroke minus baseline NIHSS. Compared to controls, there was a minor trend toward NBO benefits in short-term prognostic indices, as indicated by decreased ΔNIHSS at our defined time points. By contrast, NBO decreased Barthel Index scores between 3 and 7 months, and increased death rates at 3, 6 months, and 1 year, whereas, modified Rankin Scale scores between 3 and 6 months were unchanged. Conclusions The existing trends toward benefits revealed in this meta-analysis help us appreciate the promising value of NBO, although current evidence of NBO on improving clinical outcomes of stroke is insufficient. Well-designed multi-center clinical trials are encouraged and urgently needed to further explore the efficacy of NBO on brain protection.